Millennial’s Residential Design Principle & Basic Model To Improve Work- from-Home Performance Through Mindfulness Practices - Kartiansmara Lilih Purnaumbara (Journal of Architectural Research and Design Studies, 2023)
Since the pandemic COVID-19 outbreak in 2020, it appears that the entire world has been forced to become acquainted with working from home as a new working concept. One of the dominant challenge in implementing work-from-home comes from decline of work performance caused by incapability to cognitively focus on several task at once. Millennial as a dominant productive age range in Indonesia are facing this continuously emerging problems, considering work-from-home working culture and flexible working are believed to be a future of work culture. When implementing work-from-home, millennials face the challenge to improve work performance, one of which is through mindfulness practices to help boost work performance. Through a literature review and design by research, this study seeks to identify a home and workspace design application model that accommodates mindfulness practices. Mindfulness practices are accommodated through flexible spatial planning, building materials with various texture, window openings in the workspace are strategically adjacent to green garden, green spaces with wide variety of colour, shape, and textures, and then the principle are applied in a residential models that fit the preferences for the millennial generation Keywords: millennial house design; mindfulness; workspace; work performance